1996
DOI: 10.1046/j.1365-2265.1996.00650.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Bauman variant in Kallmann’s syndrome

Abstract: Three patients with idiopathic hypogonadotrophic hypogonadism and 2 with Kallmann's syndrome had variable degrees of GnRH deficiency. One patient with Kallmann's syndrome had apparently normal GnRH activity, which remained normal 5 months later. This patient appears to have the Bauman variant of Kallmann's syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
0
7
0
3
Order By: Relevance
“…However, this may be an underestimate as KS patients are not routinely reassessed off replacement therapy. Men with 'variant' KS may unwittingly continue on long-term treatment; indeed, Kadva et al (1996) identified one case during a study of gonadotrophin pulsatility in IHH. Other patients may simply discontinue treatment therapy, realising that it is no longer necessary, and drop out of specialist follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…However, this may be an underestimate as KS patients are not routinely reassessed off replacement therapy. Men with 'variant' KS may unwittingly continue on long-term treatment; indeed, Kadva et al (1996) identified one case during a study of gonadotrophin pulsatility in IHH. Other patients may simply discontinue treatment therapy, realising that it is no longer necessary, and drop out of specialist follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…This was followed by a report of reversal and proven paternity in a fertile eunuch male (36). In the subsequent two decades, additional case reports emerged documenting reversals (37) including fertility/conception (38,39,40) and two series were published demonstrating pulsatile LH secretion in a subset of CHH men following cessation of treatment (41,42). The first estimate of prevalence of reversal came from Quinton and et al (43) who depicted five cases among a retrospective cohort of 76 CHH patients revealing a prevalence of 5%.…”
Section: Chh Reversibilitymentioning
confidence: 99%
“…di Kadva et al . (1995) suggested a term ‘Bauman variant of Kallmann's syndrome’ after Bauman's description of such a patient (Bauman , 1986).…”
Section: Kallman's Syndrome: Is It Always For Life?mentioning
confidence: 99%